A risk analysis model for radioactive wastes - Kulahci, Fatih (Elsevier Science Bv, 2011)
Hazardous wastes affect natural environmental systems to a significant extend, and therefore, it is necessary to control their harm through risk analysis. Herein, an effective risk methodology is proposed by considering their uncertain behaviors on stochastic, statistical and probabilistic bases. The basic element is attachment of a convenient probability distribution function (pdf) to a given waste quality measurement sequence. In this paper, (40)K contaminant measurements are adapted for risk assessment application after derivation of necessary fundamental formulations. The spatial contaminant distribution of 40K is presented in the forms of maps and three-dimensional surfaces. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Potassium wastes; Risk analysis; Risk assessment; Distribution function